THE INFLUENCE OF FINANCIAL KNOWLEDGE, FINANCIAL EXPERIENCE AND FINANCIAL BEHAVIOR ON FINANCIAL LITERACY IN JAKARTA STUDENTS - Damayanti, Ana; Putra, Adrie (Journal Of Sharia Banking, 2025)
This study aims to analyze the effect of the influence of Financial Knowledge, Financial Experience, Financial Behavior on Financial Literacy in Jakarta Utara City Students. This study uses a survey method because this study uses sample data taken from a specific population. The population in this study were West Jakarta Utara City Students, totaling 100 people. The sample in this study used purposive sampling method. The data processing and analysis techniques used are descriptive statistical analysis, validation test, reliability test, classical assumption test, using normality test, multicollinearity test, heteroscedasticity test, autocorrelation analysis, multiple linear regression analysis, multiple correlation coefficient analysis, and autocorrelation test, hypothesis testing, simultaneous test (F test), partial test (t test), coefficient of determination test (?2). The results of this study indicate that simultaneously the variables Financial Knowledge, Financial Experience, Financial Behavior have a significant effect on Financial Literacy. Partially, the variables Financial Knowledge, Financial Experience, Financial Behavior have a positive and significant effect on Financial Literacy.